Unfolding the Subtitling Strategies of Imperative Sentences in Gie Movie - Ni Luh Putu Setiarini; Zahwa Ayu Maptuha; Ricky Perdana (ITScience (Information Technology and Science), 2024)
Studies on imperative sentences have been conducted by many scholars, yet there are still a small number of researches investigating on the subtitle strategies of Indonesian imperative sentences into English. The aims of this study encompassed the classification of imperative sentences found in the subtitle of a movie and the identification of subtitling strategies applied in transferring the imperative sentences. The data were collected from an Indonesian movie entitled Gie. It was a movie directed by Riri Reza. The method applied in was descriptive qualitative. To meet the objectives of the study, Swan’s theory was chosen to classify the imperative sentences and Gottlieb’s theory was applied in analyzing the strategies of subtitling. The results revealed that there are 92 data of imperative sentences. They were transferred into five types of imperative sentences. Those are affirmative imperative, subject-with imperative, let imperative, emphatic imperative, and do(n’t) be imperative. Out of the five imperative sentence types, affirmative imperative along with subject-with imperative and let imperative are the three most common ones. Meanwhile, six subtitling strategies were identified, which are paraphrase, expansion, transfer, imitation, decimation, and condensation strategy. The three most common strategies found are expansion, paraphrase, and decimation.